Electronic structure optimization boosts Pd nanocrystals for ethanol electrooxidation realized by Te doping. Issue 31 (7th July 2022) - Zhang, Qiang; Wang, Kangqiang; Zhang, Mingqing; Chen, Ting; Li, Luyan; Shi, Shuhua; Jiang, Rongyan
Abstract : Te doping greatly modifies the electronic structure of Pd and promotes the electrocatalytic performance towards EOR. Abstract : Driving ethanol electrooxidation in fuel cells is a promising technology for realizing the effective conversion of biomass energy into renewable electrical energy. However, it is still a challenge to broaden the application of fuel cells due to the limitation of effective electrocatalysts. Herein, we have proposed the design and synthesis of an advanced nonmetal-doped Pd nanocrystal catalyst for promoting the electrocatalytic ethanol oxidation reaction (EOR), in which the incorporation of nonmetal Te not only effectively modifies the electronic structure of Pd to enhance the intrinsic activity of the catalyst but also significantly boosts the further oxidation of intermediates, thereby promoting the electrocatalytic properties. Significantly, a mass activity of 1203 mA mgPd −1 for the optimized PdTe nanocrystals (NCs) has been realized, which is 4.7- and 2.5-fold enhancements as compared to the Pd NCs (255.4 mA mgPd −1 ) and commercial Pd/C (485 mA mgPd −1 ), respectively, presenting a promising electrocatalyst for fuel cells.